New Insights beyond Established Norms: A Scoping Review of Genetic Testing for Infertile Men - Kalantari, Hamid; Sabbaghian, Marjan; Vogiatzi, Paraskevi; Colpi, Giovanni M.; Sadighi Gilani, Mohammad Ali (Urology Journal, 2024)
Purpose : From a diagnostic standpoint, certain approaches to genetic screening in clinical practice remain ambiguous in the era of assisted reproduction. Even the most current guidelines do not provide definite guidance on testing protocols, leaving clinicians to carefully determine which tests best serve patients struggling with infertility. The lack of uniformity in the current practice of male fertility evaluation can prove to be quite costly, thus necessitating healthcare practitioners to carefully appraise the necessity and weigh the advantages against potential economic and psychological detriments. The objective of this review is to map the existing literature on the general topic of the clinical indications of routine karyotyping and/or AZF screening in infertile men, identify key concepts, determine where the gaps are, and lastly, provide an overview of the conclusions drawn from a body of knowledge that varies widely in terms of methodologies or disciplines. Materials and Methods : A thorough search was conducted for the published findings up until July 2023, utilizing PubMed (MEDLINE). This comprehensive search involved the use of specific search keywords, either individually or in combination. The search terms employed were as follows: “Karyotype”, "Klinefelter" or "KS" or "47,XXY", "AZF" or "Azoospermi*" and/or "microdeletion*" in the title or abstract. Once the titles and abstracts of selected articles were obtained, the complete texts of linked papers were meticulously scrutinized. Results : A total of 191 records were identified from PubMed. During screening, 161 records (84.3%) were eliminated. Finally, 30 papers were included in this scoping review, which was conducted in 18 countries. The number of sequence tag sites (STSs) used in the studies varied from 5 to 59. The rate of AZF deletions among patients with NOA ranged from 1.3% to 53%. The mean frequency was estimated to be 5.6%. The rate of YCM among patients with XXY karyotype was nil in 19 out of 30 studies (63%), whilst, in the remaining studies, the rate varied from 0.8% to 67%. Conclusion : This review provides insights into managing male infertility. The presence of spermatozoa in ejaculation and successful surgical retrieval cannot be excluded for individuals with AZFb/AZFbc microdeletions. Screening for Y chromosome microdeletions is not needed for mosaic or classic KS. Only 1% of individuals with sperm concentration exceeding 1×106 sperm/mL and less than 5×106 sperm/mL exhibit AZF microdeletions; therefore, testing referral for such populations may need reassessment. Individuals with mosaic monosomy X karyotype and certain chromosomal anomalies should be referred for AZF deletion screening. These findings have implications for male infertility management and future research.